Biodiversity assessment of Yunnan province based on the pressure-state-response model - Yu, Fang; Peng, Fei; Tang, Ze; Ma, Guoxia; Xu, Xiangyu; Zeng, Xiwen; Guo, Peipei (Frontiers in Ecology and Evolution, 2025)
Biodiversity is the foundation of human survival, and its accurate assessment is a prerequisite for effective conservation and sustainable use. Most studies only assessed the state of biodiversity, but lacked a comprehensive understanding of the pressures and responses of biodiversity. In this paper, we took Yunnan Province (Yunnan) as a pilot area and constructed a comprehensive assessment system of biodiversity pressure-state-response (PSR) to comprehensively evaluate biodiversity in Yunnan. The results showed that: (1) Yunnan was one of the richest regions in the world in terms of biodiversity resources, and among the 16 cities and prefectures, Honghe Hani and Yi Autonomous Prefecture (Honghe), Nujiang Lisu Autonomous Prefecture (Nujiang), and Xishuangbanna Dai Autonomous Prefecture (Banna) ranked in the top three for biodiversity state index; (2) From 2010 to 2020, the pressure on biodiversity in Yunnan decreased by 19%, with only a slight increase in the biodiversity pressure index in Nujiang; in 2020, Kunming City (Kunming) faced the greatest pressure on biodiversity, scoring 2.21, while Diqing Tibetan Autonomous Prefecture (Diqing) had the least pressure, scoring 0.32; (3) Diqing had the highest biodiversity response index of 1.46, while Lincang City (Lincang) had the lowest response index of 0.61. Most of cities and prefectures had not shown good balance and consistency in their responses to biodiversity conservation in Yunnan Province. (4) Considering the comprehensive PSR assessment results, Nujiang had the highest biodiversity score, while Kunming had the lowest. The study comprehensively evaluated the biodiversity state and the main pressures faced by each city and prefecture in Yunnan, and the findings can provide theoretical support for the assessment and policy formulation of biodiversity conservation in Yunnan and the indicator system and assessment methods developed in the paper have reference significance for biodiversity assessment and management in other similar areas in the international arena.